Carbonized sawdust based solar absorber in a solar still for seawater desalination - Wong Min Jin Karen; Peter Advent Stephen; Zhipeng Wang; Bih Lii Chua; Willey Y. H. Liew; Melvin Gan Jet Hong (Wiley Online Library, 2024)
Current industrial technologies for seawater desalination involve high cost and energy consumption, that is, distillation and reverse osmosis, where these technologies are difficult to implement especially in developing countries. A cost-effective, environmental-friendly, and sustainable technology is essential in providing alternative methods for generation of clean water. Solar vapor generation is one of the potential green technologies in generating clean water, where the production and collection of clean water is made possible by using a solar absorber in a solar still. The practicality and performance of the carbonized sawdust based solar absorber in a solar still for the seawater desalination towards clean water generation was conducted outdoors with gradual enhancement on the solar still setup. The enhanced solar still with reflective surface and external thermal insulator improved the solar absorber performance, in contrast to the evaporation of the bulk seawater only and using solar absorber in the solar still without any enhancement. The average efficiency and evaporation rate of the solar absorber in the enhanced solar still was recorded at 61.5% and 0.98 kg m2 h1, respectively. The pH (7.52) and salinity (10 ppm) of the collected clean water meets the standard of safe water by the World Health Organization.